2003
DOI: 10.1128/aem.69.8.4942-4950.2003
|View full text |Cite
|
Sign up to set email alerts
|

Use of 16S-23S rRNA Intergenic Spacer Region PCR and Repetitive Extragenic Palindromic PCR Analyses of Escherichia coli Isolates To Identify Nonpoint Fecal Sources

Abstract: Despite efforts to minimize fecal input into waterways, this kind of pollution continues to be a problem due to an inability to reliably identify nonpoint sources. Our objective was to find candidate source-specific Escherichia coli fingerprints as potential genotypic markers for raw sewage, horses, dogs, gulls, and cows. We evaluated 16S-23S rRNA intergenic spacer region (ISR)-PCR and repetitive extragenic palindromic (rep)-PCR analyses of E. coli isolates as tools to identify nonpoint fecal sources. The BOXA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 44 publications
5
67
0
1
Order By: Relevance
“…Thus, there was a 21.7% reduction in the average rate of correct classification by using the unique DNA fingerprint library, relative to that seen with the complete library and less than we and others have previously reported with smaller libraries of E. coli strains containing duplicate DNA fingerprints from the same individual animal (4, 6, 23). Our results indicate that the clonal nature of E. coli (11,20,33) originating from the same source animal artificially biases the average rate of correct classification, alters the fidelity of the database, and overestimates the ability of the database to assign isolates to their correct source group. Influence of library size on usefulness of DNA fingerprint libraries.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, there was a 21.7% reduction in the average rate of correct classification by using the unique DNA fingerprint library, relative to that seen with the complete library and less than we and others have previously reported with smaller libraries of E. coli strains containing duplicate DNA fingerprints from the same individual animal (4, 6, 23). Our results indicate that the clonal nature of E. coli (11,20,33) originating from the same source animal artificially biases the average rate of correct classification, alters the fidelity of the database, and overestimates the ability of the database to assign isolates to their correct source group. Influence of library size on usefulness of DNA fingerprint libraries.…”
Section: Resultsmentioning
confidence: 91%
“…Also, ribotyping is suitable in epidemiological studies for determining relatedness and discrimination of strains [25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies have employed DNA fingerprinting to discern characteristic patterns and associations among E. coli strains in order to classify the strains according to the host from which they were derived (7,11,17,23,27,31). Overall, studies that have assessed the relationships among strains by either cluster analysis (17) or discriminant analysis using banding patterns (7,27) have found that strains from a host source do not form an exclusive group of genetically similar strains but rather can display a wide range of diversity.…”
mentioning
confidence: 99%